Free Nutritious Meals as A Constitutional Right: Budgetary Politics, Social Justice, and Implementation Challenges in Indonesia - Khoirul Hadi al Asy Ari Hadi; Syafril Wicaksono; Nikmatul Munawiroh (Journal of Communication and Da'wah, 2026)
Free Nutritious Meal Program (MBG) launched by the government marks a new chapter in fulfilling the basic rights of citizens, especially school-age children. From a constitutional perspective, the right to nutritious food is an integral part of the guarantee of social rights as stipulated in the 1945 Constitution. However, the implementation of the MBG is not only technocratic but also fraught with budget politics that often give rise to a tug-of-war between fiscal stability and social justice. The background of this problem is rooted in the question of whether the MBG truly functions as an instrument of distributive justice or is merely a populist project with limited effectiveness. The research gap arises because previous studies have focused more on the technical aspects of implementing the food program, while the normative-philosophical approach linking the MBG with constitutional rights and budget politics is still rarely discussed. The novelty of this research lies in the analysis of the MBG as a legal instrument that examines the extent to which fiscal politics is able to realize substantive social justice, not just short-term political stability. The formulation of this research problem is first: How can the MBG be interpreted as part of the fulfillment of citizens' constitutional rights from the perspective of budgetary legal politics? Second, what are the normative and implementative challenges of the MBG in realizing the principles of social justice in Indonesia? Preliminary results indicate that the success of the MBG is largely determined by the political alignment of fiscal law oriented towards distributive justice and transparent oversight. Without this, the program risks becoming both a fiscal burden and a tool for reproducing social injustice.